2007
DOI: 10.1111/j.1467-9485.2007.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term Contracts Regulations and Dynamic Labour Demand: Theory and Evidence

Abstract: We present a dynamic labour demand model where we evaluate the impact of employment regulations on permanent and temporary employment. We consider three different kinds of regulations, namely firing costs, hiring costs and a constraint on temporary contracts. These regulations differently affect the size and composition of employment. The theoretical results are interpreted and questioned on the basis of empirical evidence on the employment effects of the regulation reforms that occurred in the major European … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
2
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 23 publications
5
65
2
5
Order By: Relevance
“…Boeri, 2011;Cahuc and Postel-Vinay, 2002;Freeman, 2007;Kahn, 2007;King and Rueda, 2008;Lucifora, 2000;Nunziata and Staffolani, 2007). While institutions have an undeniable effect on labour market outcomes, their explanatory power is limited.…”
mentioning
confidence: 99%
“…Boeri, 2011;Cahuc and Postel-Vinay, 2002;Freeman, 2007;Kahn, 2007;King and Rueda, 2008;Lucifora, 2000;Nunziata and Staffolani, 2007). While institutions have an undeniable effect on labour market outcomes, their explanatory power is limited.…”
mentioning
confidence: 99%
“…If firms succesfully use the former to dipose of sufficient labour when demand is high, this will positively affect the relative productivity of FTC workers: contrary to their colleagues with PCs, they only appear on the payroll in busy periods with hikes in per hour production, whereas PC workers are also in the firm when business is slow and per hour output is sluggish. Nunziata and Staffolani (2007) developed a model in which the probability of using FTCs depends on the volatility in product demand. In general, labour adjustment costs (i.e.…”
Section: Demand Fluctuations and Adjustment Costsmentioning
confidence: 99%
“…For employers it can therefore be attractive to hire women on such risk-free temporary contracts. The attractiveness of using temporary employment for outsiders does not only depend on the degree to which regular employment is protected, but also on the level of regulation of temporary contracts (Nunziata and Staffolani, 2007). Kahn (2010) has shown that increased deregulation of temporary work has led to an overall increase of temporary employment amongst the employed population.…”
Section: Temporary/fixed-term Employmentmentioning
confidence: 99%